The Influence Of Work Environment, Work Discipline And Motivation on The Performance of Civil Servants at The Inspectorate of East Java Province - Citra Puspita Sari; Sri Rahayu; Sundjoto Sundjoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Institutions and organizational development depend on human resources. Humans always play an active role in every organizational activity because humans are planners, actors and determinants of the realization of organizational goals. The aim of this research is to test, prove and analyze the influence of the work environment, work discipline and motivation on employee performance. This research uses primary data in the form of distributed questionnaire data. The sample used was 45 respondents, sampling criteria were used. The analysis used in this research is SEM analysis. Based on the research results, it can be concluded that work discipline and motivation variables influence employee performance, while environmental variables influence employee performance. Thus, the delivery and suggestions, namely the implementation of an online attendance system, can potentially increase the level of employee discipline, due to more effective monitoring of attendance and absence. This system can make a positive contribution to employee performance by providing accurate data on whereabouts, enabling management to plan and optimize task assignments. Involve employees in system development and implementation to ensure that the system meets their needs and adds value to daily tasks. Keywords: Work Environment, Work Discipline, Motivation And Performance, Employee Performance.